1993
DOI: 10.1155/1994/70629
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Laparoscopic Cholecystectomy

Abstract: vomiting in the early post-operative period. Seventy-nine patients (81%) were able to be discharged home within 4 to 6 hours of surgery, with only one patient requiring readmission to hospital because of the onset of nausea and vomiting. There were no post-operative complications attributable to the outpatient experience. We believe this approach to elective gallbladder pathology can be safely accomplished in selected patients and will be increasingly utilized in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…1 2 Evidence supporting safety of major DCS including laparoscopic cholecystectomy is predominantly composed of case series of selected patients. [3][4][5][6][7][8] Universal extrapolation of published experience is potentially dangerous because poor and unacceptable outcomes have been reported. 10 11 The risk may be even more in economically deprived countries where low literacy rates, lack of reliable and efficient transport, absence of organised referral patterns, poorly developed communication systems, underdeveloped primary health care services, and absence of community nursing have prevented the successful introduction of major surgical operations as day care surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 Evidence supporting safety of major DCS including laparoscopic cholecystectomy is predominantly composed of case series of selected patients. [3][4][5][6][7][8] Universal extrapolation of published experience is potentially dangerous because poor and unacceptable outcomes have been reported. 10 11 The risk may be even more in economically deprived countries where low literacy rates, lack of reliable and efficient transport, absence of organised referral patterns, poorly developed communication systems, underdeveloped primary health care services, and absence of community nursing have prevented the successful introduction of major surgical operations as day care surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Several published studies have testified to the safety and feasibility of day care laparoscopic cholecystectomy (DCLC). [3][4][5][6][7][8] These reports, however, emanate from developed countries with well established norms for day care surgery with rigorously monitored outcomes. [3][4][5][6][7][8] The reported safety of laparoscopic cholecystectomy cannot therefore be universally extrapolated to surgical practice everywhere.…”
mentioning
confidence: 99%
“…A crucial aspect in the development of a safe Day Care program is the criteria for patient selection. Robinson"s et al [44] reported their experience in a public academic institution where they achieved outpatient laparoscopic cholecystectomy in 70% of unselected patients and they have identified ASA classification, procedural duration and surgery start time as a factor associated with failure of day care program. Some authors have come to the conclusion that appropriate patient selection lowers failure rate and patients most likely to fulfill the criteria of day care laparoscopic cholecystectomy are ASA grade I,II and younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comparision showing success, failure and readmission rates of various studies (table 9) Study Total patients Success rate(%) Failure rate(%) Readmission rate(%) Selim et al [58] 200 90% 10% 10% Taylor et al [40] 108 87% 13% na Robinson et al [44] 387 70% 30% na S.S. Bal et al [45] 313 92% 8% 3% Ibramin et al [46] 70 100% 0% 1.5% Chauhan et al [47] 287 96% 4% 3% Athar et al [54] 50 92% 8% 2% Kaman et al [60] 106 95% 5% na Present study 50 90% 10% 4%…”
Section: Discussionmentioning
confidence: 99%
“…Prompt surgical management of confirmed symptomatic cholelithiasis is the standard of care and the treatment of choice, provided no contraindication exists [7]. Laparoscopic cholecystectomy has evolved as the gold standard and has been shown to reduce total hospital charges [10]. The untimely manner in which the standard treatment of symptomatic cholelithiasis is applied to MediCal patients is not equitable under the current system.…”
Section: Discussionmentioning
confidence: 99%